2000
DOI: 10.1215/00141801-47-2-423
|View full text |Cite
|
Sign up to set email alerts
|

Women, Kin, and Catholicism: New Perspectives on the Fur Trade

Abstract: This article focuses on four Native women who were Christian converts and married French fur traders. As ''cultural mediators'' and ''negotiators of change'' they mediated the face-to-face exchange of goods for peltry in the western Great Lakes through Catholic kin networks that paralleled and extended those of indigenous society. Their reliance on kinship and Catholicism suggests new ways to study women's involvement in the trade and to reassess how trade and religion affected Indian communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Given what most historians had written about the mixed race families in places like Kaskaskia, I expected these individuals to be members of wealthy fur trade families (Peterson 1981;Kirk 1983;Sleeper-Smith 2000). To my surprise, I found that these people at the center of this network were not fur traders, by and large.…”
Section: Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Given what most historians had written about the mixed race families in places like Kaskaskia, I expected these individuals to be members of wealthy fur trade families (Peterson 1981;Kirk 1983;Sleeper-Smith 2000). To my surprise, I found that these people at the center of this network were not fur traders, by and large.…”
Section: Practicementioning
confidence: 99%
“…Rather, marriage and kinship networks functioned to give Frenchmen the identity needed to operate in what remained very much an Indian habitus. If anything, as many historians have demonstrated, these kinship connections allowed Frenchmen to "go native" (Barr 2007;DuVal 2006;Sleeper-Smith 2000, 2001DeMaillie 1998;Bohaker 2006;Brooks 2002).…”
mentioning
confidence: 99%
“…Indigenous women may have been seen as suitable partners, acting as "cultural brokers" (McEwan, 1991, p. 33;Sleeper-Smith, 2000) for European men who arrived on New Zealand's shores as sealers, whalers, and traders. However, indigenous women were not sanctioned as wives for missionaries.…”
Section: The Role Of Missionary Womenmentioning
confidence: 99%
“…In these instances, Maori women acted as, in Susan Sleeper-Smith's words, 'mediators between cultural groups'. 11 Much later, at a time when the Maori population had been far outstripped by Pakeha, the anthropologist John Harre undertook an in-depth study of 'interracial' marriages in 1960s Auckland, New Zealand's largest city, stating: 'the rate of marriage is likely to increase and this will be one factor in a context of improving race relations in New Zealand'. 12 Within a decade racial politics in New Zealand became very fraught as Maori increasingly drew attention, in more confrontational ways than before, to their history of dispossession.…”
mentioning
confidence: 99%